Manajemen Strategi Kepala Sekolah dalam Membangun Budaya Religius di SDN 3 Lenek - Tapaul, Tapaul; Sobry, M.; Thohri, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This research aims to investigate the strategic management of the school principal in building a religious culture at SDN 3 Lenek. The background is the importance of strengthening religious values in the educational environment, especially at the primary level, to foster strong character in students. The research method used is a qualitative approach with a single case study. Data collection techniques are conducted through participatory observation, interviews with the principal, teachers, and parents of students, as well as document analysis. Data are analyzed inductively through the process of reduction, display, and verification. The results show that the school principal employs various management strategies, including establishing the school's vision and mission, actively involving stakeholders, developing religious programs, and implementing religious values in daily activities. This creates a learning environment that promotes religious values and strengthens the school's identity. The implications of this research underscore the importance of the principal's role in shaping a religious culture in primary schools, as well as the need for support from all relevant parties.